Dual modal imaging agents based on chromophore-bearing DTPA analogues. Issue 61 (4th August 2017) - Sathiyajith, CuhaWijay; Hallett, Andrew J.; Amoroso, Angelo J.; Edwards, Peter G.
Abstract : Two new DTPA analogues, centrally (L 1 ) and terminally (L 2 ) functionalised with a 1, 8-naphthalimide chromophore, have been successfully prepared and fully characterized. Abstract : Two new DTPA analogues, centrally (L 1 ) and terminally (L 2 ) functionalised with a 1, 8-naphthalimide chromophore, have been successfully prepared and fully characterized. Their Gd(iii ) complexes have also been prepared and evaluated for their ability to act as dual modal contrast agents (MRI/OI). The highly reproducible R 1 relaxivity ofL 1 (8.10 ± 0.21 mM −1 s −1, 25 °C and 30 MHz) is markedly higher than other DTPA based contrast agents. The Gd(iii ) complexes of bothL 1 andL 2 have been evaluated as luminescence probes; the ligand based fluorescence is not quenched upon complexation.